De/constructing the Academic Hood: Reflexive Considerations for Doctoral Researcher Socialization for International Research - Vital, Louise Michelle; Yao, Christina W. (Journal of International Students, 2021)
Doctoral education is often lauded as a site of academic socialization and research training for nascent scholars. However, discussions of socialization seldom problematize the dangers of intellectual imperialism and methodological nationalism inherent in doctoral researcher socialization. As such, the traditional socialization practices for doctoral students in the United States (U.S.) must be interrogated and expanded to move towards equitable practices for research, especially for students conducting international research. Using social and spatial positioning as our conceptual framing, we problematize and question current approaches and practices to doctoral researcher training in the U.S. We use the academic hood, which is granted upon successful completion of doctoral studies, as a metaphor to reconsider how to reflect upon and navigate power dynamics and knowledge production within the U.S. academy.